Natural ink production and printability studies for smart food packaging - ÖZCAN, ARİF; ARMAN KANDIRMAZ, EMİNE (WILEY, 2020)
Versatile smart packages provide information on the freshness of the content and help protect the content from microorganisms. In this sense, in this study both natural antimicrobial properties and pH sensitive natural dyes were obtained from red beet. Inks were prepared and printed using this dye and their suitability for smart packaging was investigated. For this purpose, red beet was cut into small sizes and mixed separately in ethanol and water (1:2) at 200 rpm. The betaine dye was taken up in solvent. These solvents were removed with evaporator and precipitated with centrifugation and dried in a vacuum oven. The chemical structure of the obtained dye was illuminated by Attenuated Total Reflection-Fourier Transform Infrared Spectroscopy (ATR-FTIR). The color character was determined by UV spectroscopy. Pink colored natural ink was produced by using ink varnish with carboxymethyl cellulose polymer and solid dye. Screen printing was made with this ink and the color, gloss, and lightfastness characters of prints were examined. Antimicrobial effects of the obtained prints were measured against Staphylococcus aureus and Escherichia coli. Mordanting studies were performed with (KAl[SO4](2).12H(2)O) and change in color character was measured. The prints produced using the red beet extract have a yellow-orange color in the basic state; in acid cases it was determined to have a pink-purple color. In addition, it has been found that the ink prints obtained from red beet have antimicrobial properties against bacteria. Results prove that produced samples have good antimicrobial, pH indicator, and printability properties. This colorant can be used in smart food packaging.
Keywords: edible ink; natural ink; printability; smart packaging; EDIBLE FILMS; PRINTING INK; CHITOSAN; COATINGS; FRESH